Development of Puzzle Learning Media based on Local Wisdom of Maluku Culture in Teaching Social Science Learning in 4th Grade Students of SD Negeri Leahari - Mahananingtyas, Elsinora; Johannes, Nathalia Yohana; Ruhulessin, Olifia Weldi; Ritiauw, Leonid (KnE Social Sciences, 2024)
This study aims to design learning media in the form of puzzles based on the local wisdom of Maluku culture and test its feasibility. The research was done using R&D method by adapting the ADDIE model—namely Analysis, Design, Development, Implementation, and Evaluation. The results of the validator’s assessment of the puzzle obtained an average percentage of 92.5% by media experts in the category “Very Feasible” to use in learning activities. The results of the response from the teacher obtained an average percentage of 97.2% with the category “Very Feasible to Use”, while the responses from students showed the category “Very Feasible” to use with an average percentage of 91.5%. The box-shaped puzzle consists of pieces of arrangeable images that display the cultural diversity of Maluku and is made from natural materials, namely sago tree fronds or ’gaba-gaba’. The cultural diversity material contained in this puzzle includes traditional houses, clothing, and dances from Maluku Province. The puzzle was designed using Canva and Adobe Illustration. In conclusion, puzzle learning media with Maluku’s local wisdom-based is very feasible to use in learning to help teachers teach about “Cultural Diversity”. Keywords: Learning Media, Puzzle, Local Wisdom, Maluku Culture